Differences in typing forces, muscle activity, wrist posture, typing performance, and self-reported comfort among conventional and ultra-low travel keyboards. (January 2019) - Kia, Kiana; Sisley, Jonathan; Johnson, Peter W.; Kim, Jeong Ho
Abstract: This study investigated the relative impact of ultra-low travel keyboards on typing force, muscle activity, wrist posture, typing performance, and self-reported comfort/preference as compared to a conventional keyboard. In a repeated-measures laboratory-based study, 20 subjects were invited to type for 10 min on each of five keyboards with different travel distances of 0.5, 0.7, 1.2, 1.6 (ultra-low travel keyboards), and 2.0 mm (a conventional keyboard). During the typing sessions, we measured typing force; muscle activity in extrinsic finger muscles (flexor digitorum superficialis and extensor digitorum communis), shoulder (trapezius) and neck (splenius capitis); wrist posture; typing performance; and self-reported comfort/preference. While using the ultra-low travel keyboards, subjects typed with less force and wrist extension, and had more ulnar deviation (p's < 0.0001) compared with conventional keyboard. However, these differences in typing forces were less than 0.5 N and less than 4° for both wrist extension and ulnar deviation. The general trend of data did not show any consistent or substantial differences in muscle activity (less than 2 %MVC) and typing performance (<5 WPM in speed; < 3% in accuracy), despite the observed statistical difference in the finger flexors and extensors muscle activity (p's < 0.19) and typing performance (p < 0.0001). However, the subjects preferred using conventional keyboards in most of the investigated self-reported comfort and preference criteria (p's < 0.4). In conclusion, these small differences indicate that using ultra-low travel keyboards may not have substantial differences in biomechanical exposures and typing performance compared to conventional keyboard; however, the subjective responses indicated that the ultra-low keyboards with the shortest key travel tended to be the least preferred. Highlights: Typing biomechanics, performance, and usability were compared between ultra-low travel and a conventional keyboard. Differences in typing biomechanics and performance were practically small between the keyboards. Subjective comfort and usability ratings were higher with a conventional keyboard compared to ultra-low travel keyboards.